SOSIALISASI PENDIDIKAN ANTIKORUPSI GUNA MENCIPTAKAN GENERASI MUDA BERMUTU DI SMKS HARAPAN BARU, BEKASI UTARA - Nasaruddin Siregar; Nita Komala Dewi; Sari Endah Nursyamsi (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
The purpose of the PKM activity is to be able to strengthen the personality of students which will add a plus value to the educational process that has been carried out by the school by introducing anti-corruption education. In accordance with the problems experienced by the partners of SMKS Harapan Baru, Bekasi, namely the problems experienced by partners namely 1) There is no understanding from students related to the insights of religious norms contained in learning. 2) Partners do not yet have an independent learning teaching curriculum related to anti-corruption education. 3) The need to provide information regarding anti-corruption education to students to produce quality human resources. The method of carrying out the activity was by providing counseling in the form of lectures and FGD which was held on Wednesday, July 20, 2022 in the Harapan Baru Vocational High School hall, Bekasi, with 30 student representatives participating. The results of the activity are increasing participants' knowledge about corruption, increasing the patriotic spirit of students/wis, helping partners in adding anti-corruption education as one of the MBKM curricula and as motivation for partners to be able to carry out activities that can create quality human resources for the world of education.